Pandangan Terhadap Fenomena Cyberbullying di Kalangan Masyarakat +62 - Dinda Amelia; Fauziah Juliandina Tanjung; Miracle Sinaga; Nailah Dhia Salma; Renita Maulidya Tarigan; Silvia May Sharoh (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
The increasing use of social media has given rise to various forms of verbal violence, such as cyberbullying. Cyberbullying is a phenomenon in which individuals use social media to disseminate degrading messages, threats, or insults to individuals or groups. Its relevance to Pancasila as the foundation of the Indonesian state is crucial, given the principles of Pancasila, such as Just and Civilized Humanity, Indonesian Unity, and Social Justice for All the People of Indonesia. This study aims to examine the perception of cyberbullying among the +62 community. This research employs a quantitative approach. Data collection is conducted through the distribution of questionnaires via Google Forms on social media. The results obtained from this research indicate that a majority of respondents agree that humor on social media and personal matters are common reasons for cyberbullying. Additionally, cyberbullying deviates from the second principle of Pancasila, where every individual has the right to live safely, peacefully, and be treated fairly and equally, regardless of physical, economic, and other differences. Efforts to address cyberbullying include individual ethical awareness and behavior, the need for supervision and regulation in the online world, and education and awareness about the principles of Pancasila.